2020
DOI: 10.1186/s13098-019-0514-y
|View full text |Cite
|
Sign up to set email alerts
|

Association between metabolic syndrome and prognosis of breast cancer: a meta-analysis of follow-up studies

Abstract: Background: Metabolic syndrome (MetS) has been suggested to be a risk factor for many cancers, including breast cancer. However, it remains unclear whether MetS predicts poor prognosis in women with breast cancer. A meta-analysis was performed to summarize the association between MetS and clinical outcome in women with breast cancer. Methods: Cohort studies were identified by search of PubMed and Embase databases. A random-effect model incorporating the potential heterogeneity was applied to pool the results. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 49 publications
4
23
1
Order By: Relevance
“…Metabolic syndrome was diagnosed in accordance with the criteria set forth by the Chinese Diabetes Society in 2004, 9 which defines a person as having metabolic syndrome if at least three out of the following four factors as present: (1) obesity: body mass index ≥25 kg/m 2 ; (2) hyperglycemia: fasting blood glucose ≥6.1 mmol/L and/or 2-hour plasma glucose ≥7.8 mmol/L and/or previously diagnosed diabetes; (3) hypertension: systolic/diastolic blood pressure ≥140/90 mmHg and/or antihypertensive therapy; and (4) dyslipidemia: triglycerides ≥1.7 mmol/L and/or high-density lipoprotein <0.9 mmol/L in men or <1.0 mmol/L in women.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolic syndrome was diagnosed in accordance with the criteria set forth by the Chinese Diabetes Society in 2004, 9 which defines a person as having metabolic syndrome if at least three out of the following four factors as present: (1) obesity: body mass index ≥25 kg/m 2 ; (2) hyperglycemia: fasting blood glucose ≥6.1 mmol/L and/or 2-hour plasma glucose ≥7.8 mmol/L and/or previously diagnosed diabetes; (3) hypertension: systolic/diastolic blood pressure ≥140/90 mmHg and/or antihypertensive therapy; and (4) dyslipidemia: triglycerides ≥1.7 mmol/L and/or high-density lipoprotein <0.9 mmol/L in men or <1.0 mmol/L in women.…”
Section: Methodsmentioning
confidence: 99%
“…6 , 7 In addition, numerous studies have shown an association between metabolic syndrome and various cancers. 8 Importantly, due to its aggressive involvement in multiple malignancies, metabolic syndrome has been shown to serve as a prognostic indicator in various cancers, including breast cancer, 9 gastric cancer, 10 colorectal cancer, 11 , 12 oesophageal squamous cell carcinoma, 13 prostate cancer, 14 ovarian cancer, 15 renal cancer, 16 etc. Nonetheless, even though a case-control NPC study reported that metabolic disorder increases the carcinogenesis risk, 17 the impact of metabolic syndrome on NPC outcomes and its relevant mechanism remain vastly elusive.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis evaluated nine cohort studies, where metabolic syndrome relates to a higher risk of breast cancer recurrence (RR = 1.52, p = 0.02). Also, breast cancer patients with metabolic syndrome had an increased risk for cancer mortality (RR = 1.80, p < 0.001) Li [54]. Most of the study population of the present research had at least one element of metabolic syndrome (70.71 %), and this could increase the probability of a bad prognosis.…”
Section: Modifiable and Non-modifiable Risk Factors In The Study Cohortmentioning
confidence: 61%
“…Moreover, we lacked information on lifestyle factors, such as the patients’ body mass index (BMI), smoking status, and alcohol consumption although it is known that most T2D patients are overweight or obese 76 . Some studies have reported that obesity might be independently associated with poorer prognosis for BC patients 77 , and metabolic syndrome has been found to be significantly associated with an increased risk of BC recurrence 78 . A large systematic review with meta-analysis has indicated that BC patients ceasing to smoke can lower their BC-specific mortality dramatically 79 .…”
Section: Discussionmentioning
confidence: 99%